Campos maduros e campos marginais - definições para efeitos regulatórios - Câmara, Roberto José Batista (2004)
It is not possible nowadays to find in the literature a clear definition of what is a mature oil field and what is a marginal oil field. Unfortunately these concepts have been used in many cases interchangeably. This is misleading because they do not refer to the same thing. As a matter of fact it comes easily to one s mind the idea of the first as being an old field, subjected to years of water injection but still capable of producing economically, whereas for the latter the idea is different, more related to economics. The Brazilian oil industry is beginning its path toward a new scenario of opening opportunities to both big companies and small entrepreneurs eager to invest capital in new areas as well as in old fields that the stated owned Petrobras is selling at fair prices. This new scenario calls for new laws and regulations capable of offering incentives for the players, many of them without a strong background in the oil industry, but willing to play a role and profit from it. For the purpose of regulation, this means granting lower taxes and incentives to new money invested and production increases and coming up with definitions for mature and marginal oil fields. My dissertation focus on defining these terms. An extensive literature survey as well as interviews with experienced people from the oil industry were carried out. For the mature fields we came up with a relationship between the volume of oil produced and the total recoverable oil volume, which should be no less than 40%. For marginal fields the economics were the basis. We propose a new parameter EFR (Equilibrium Financial Rate), with oil market price and several production costs as its main variables. The oil field is considered marginally economical when the rate is on the interval between 5 % above and 5 % below EFR. For regulatory purposes these polemical issues are no doubt at the starting point. Our work aims to contribute for this discussion and to provide a reference for those, as ANP (Petroleum National Agency) and others, working on legislation.